Synthesis of fully bio-based and solvent free non-isocyanate poly (ester amide/urethane) networks with improved thermal stability on the basis of vegetable oils. (September 2018) - Farhadian, Abdolreza; Ahmadi, Abbas; Omrani, Ismail; Miyardan, Ahmad Babaei; Varfolomeev, Mikhail A.; Nabid, Mohammad Reza
Abstract: The purpose of this study is to synthesize non-isocyanate poly (ester amide/urethane) networks, based entirely on vegetable oil through a green method, i.e., without solvent and having any rigid and aromatic structures to improve their thermal stability. For this purpose, first, three amines were synthesized from castor oil and oleic acid. Second, carbonated sunflower oil (CSFO) was obtained by reaction of epoxidized sunflower oil with CO2 at atmospheric pressure. In the final step, CSFO easily reacted with bio-based amines by melt-blending without catalyst to give corresponding non-isocyanate polyurethane (NIPU) networks. The Fourier-transform infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), X-ray powder diffraction (XRD), differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA) and thermogravimetric analysis (TGA) techniques were applied to characterize the structural, thermal and physical features of NIPU networks. In addition, to determine the environmental stability the water absorption amount and the degradation percentage were calculated in the deionized water and phosphate saline buffer, respectively. These NIPU networks showed an excellent thermal stability ( T 5 wt% between 323 and 386 °C), low water absorption and degradation (4–10 and 1.04–1.40 wt% respectively). The results show the potential of this environmentally friendly strategy for preparing bio-based NIPU for high performances. Furthermore, the presence of an aliphatic ester group and their biodegradability nature may also make them proper for biological and/or biomedical applications. Graphical abstract: Image 1 Highlights: Green method for synthesis of non-isocyanate poly (ester amide/urethane) networks was proposed. In this method both monomers are liquid, therefore it can be used in the industry without solvent. Bio-based NIPUs were synthesized from carbonated sunflower oil and three vegetable oil-based amines. Synthesized NIPUs have high thermal stability without having any rigid and aromatic structures. The presence of an aliphatic ester group and biodegradability of NIPUs make them suitable for biomedical applications.